2014
DOI: 10.1080/10256016.2014.964233
|View full text |Cite
|
Sign up to set email alerts
|

137Cs and40K in some traditional herbal teas collected in the mountain regions of Serbia

Abstract: Herbal teas are an important part of traditional medicine in Serbia. The objective of the present study was to determine the activity concentrations of (40)K and (137)Cs in herbal tea, using the gamma spectroscopy method. The samples were collected during the period 2011-2012 in three mountain regions in Western and Central Serbia. The activity concentrations of (40)K and (137)Cs were found to be in the range of 130-1160 and 0.7-124 Bq kg(-1), respectively. The average annual effective dose equivalents from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…Two recent studies reported greater Th concentration levels ranging from 0.597 to 9.918 mg/kg [67] and from 2.46 to 14.76 mg/kg [68]. Cesium radioactivity concentration levels were reported by Oprea et al [68] and Mitrovic et al [69], however, the current study did not determine radiological risk.…”
Section: Metal(loid) Concentration Levels In Tea Plant Parts and Soilcontrasting
confidence: 58%
“…Two recent studies reported greater Th concentration levels ranging from 0.597 to 9.918 mg/kg [67] and from 2.46 to 14.76 mg/kg [68]. Cesium radioactivity concentration levels were reported by Oprea et al [68] and Mitrovic et al [69], however, the current study did not determine radiological risk.…”
Section: Metal(loid) Concentration Levels In Tea Plant Parts and Soilcontrasting
confidence: 58%
“…The artificial radionuclide 137 Cs was detected (MDA-2.9 Bq/kg) in five of the seven investigated samples. The variation of the 137 Cs content in plants is a consequence of different soil contamination and geochemical characteristics, meteorological conditions, plant species and growing conditions [10]. A similar content of 137 Cs in herbal teas from different regions of Serbia, except for blueberry tea, has been reported in a study that investigated fifteen samples of herbal teas (collected in 2018) and found that the activity concentration of 137 Cs ranged from below MDA to 24.7 Bq/kg that was measured in blueberry tea [7].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the radionuclides, herbal teas can be a source of other contaminants such as pesticides, mycotoxins, microorganisms and heavy metals [9]. Previous studies have shown that the contaminants from herbal teas are generally transferred to tea infusions in small quantities, making the infusions safe for human consumption [7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to know the level of radioactivity concentrations in tea to ensure consumer safety. The activity concentration in tea was evaluated in areas of high background radiation (Hamzah et al, 2011;Mitrovi´c et al, 2014).…”
Section: Resultsmentioning
confidence: 99%